2012
DOI: 10.1177/001979391206500104
|View full text |Cite
|
Sign up to set email alerts
|

Organizational and Individual Learning and Forgetting

Abstract: Researchers of industrial relations issues in manufacturing have long recognized that careful study of production has significant implications for labor productivity. Recent theory and analysis has shown the large influence of organizational forgetting. The authors of this study demonstrate that forgetting by workers in an establishment or line of production as a substantive characteristic of actual production processes is overstated and that alternative, simpler theoretical and empirical explanations have at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Whereas this strategy can be useful in reducing fixed costs, our results detect a lower learning process during the production phase, which implies a lower rate of reduction of production costs in the assembly of the aircraft as accumulated production increases. Our results are consistent with the ones found by Kleiner, Nickelsburg and Pilarski, who studied learning and forgetting processes in the production of the DC-9 and MD-80 aircraft which shared the same fuselage, and found that the simultaneous production of both models on the same assembly line provoked a rise in production costs [ 16 ]. This could also be the case of the F-35 Lightning II.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Whereas this strategy can be useful in reducing fixed costs, our results detect a lower learning process during the production phase, which implies a lower rate of reduction of production costs in the assembly of the aircraft as accumulated production increases. Our results are consistent with the ones found by Kleiner, Nickelsburg and Pilarski, who studied learning and forgetting processes in the production of the DC-9 and MD-80 aircraft which shared the same fuselage, and found that the simultaneous production of both models on the same assembly line provoked a rise in production costs [ 16 ]. This could also be the case of the F-35 Lightning II.…”
Section: Introductionsupporting
confidence: 92%
“…Interestingly, Kleiner, Nickelsburg and Pilarski reported the cases of the DC-9 and MD-80 aircraft production [ 16 ]. They pointed out that the DC-9 and the MD-80 shared the same fuselage cross-section, but the wing, electronics, and systems integration were different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important strategic value of organizational learning is to surpassing learning barriers, creating new knowledge and building self-adapt and innovative learning organization. It is organizational learning's profound sense of reality (Kleiner, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This position was reinforced by empirical contributions in the aircraft industry (Kleiner et al, 2012) that found that managers and first-line supervisors contributed to the maintenance of institutional memory during a strike by replacing workers so that knowledge loss was reduced.…”
Section: Accidental Forgetting: Preserving Organizational Memorymentioning
confidence: 99%